2010
DOI: 10.1016/j.bpj.2010.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Modulation of Integrin-Mediated Cell Adhesion

Abstract: In response to external stimuli, cells modulate their adhesive state by regulating the number and intrinsic affinity of receptor/ligand bonds. A number of studies have shown that cell adhesion is dramatically reduced at room or lower temperatures as compared with physiological temperature. However, the underlying mechanism that modulates adhesion is still unclear. Here, we investigated the adhesion of the monocytic cell line THP-1 to a surface coated with intercellular adhesion molecule-1 (ICAM-1) as a functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 59 publications
3
47
0
Order By: Relevance
“…Hence, it stands to reason that cells in our measurements do not display a greater compliance after myosin inhibition. Such hypothesis is supported by the work of Rico et al (56), who varied the adherence of cells by changing the ambient temperature and measured cell compliance using atomic force microscopy. They reported an increase in cell compliance with the loss of adhesion, which is highly connected to the loss of stress fibers in less adherent cells.…”
Section: Discussionmentioning
confidence: 77%
“…Hence, it stands to reason that cells in our measurements do not display a greater compliance after myosin inhibition. Such hypothesis is supported by the work of Rico et al (56), who varied the adherence of cells by changing the ambient temperature and measured cell compliance using atomic force microscopy. They reported an increase in cell compliance with the loss of adhesion, which is highly connected to the loss of stress fibers in less adherent cells.…”
Section: Discussionmentioning
confidence: 77%
“…Here all of the cells were cultured with the same cell growth medium to avoid the influence of cell growth medium. Besides, the temperature can also influence the cell mechanics [13,14,36,37]. Rico et al [13] have measured the Young's modulus of THP-1 cells (human monocytic leukemia cell line) at three temperatures (16, 24 and 37°C), showing that the cellular Young's modulus significantly decreased as the temperature increased.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the temperature can also influence the cell mechanics [13,14,36,37]. Rico et al [13] have measured the Young's modulus of THP-1 cells (human monocytic leukemia cell line) at three temperatures (16, 24 and 37°C), showing that the cellular Young's modulus significantly decreased as the temperature increased. Spedden et al [14] have measured the Young's modulus of neuron cells prepared from embryonic rat at room temperature (25°C) and 37°C, also showing that the increase of temperature can cause the cell softening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that mild hypothermia could inhibit cells adhesion in flow when the density of adhesion molecules was kept constant. First, Rico and coworkers (41) observed that the work required to detach an atomic force microscope (AFM) cantilever tip functionalized with human ICAM-1-Fc from the cells' surface decreased dramatically from 37ºC to 16ºC. They further found it was due to two main factors.…”
Section: Discussionmentioning
confidence: 99%